2021
DOI: 10.1182/blood-2021-149769
|View full text |Cite
|
Sign up to set email alerts
|

Romiplostim, Low-Dose Rituximab and High-Dose Dexamethasone Combination in Newly Diagnosed Immune Thrombocytopenia: Another "Total Therapy" Pilot Study

Abstract: Background: Primary immune thrombocytopenia (ITP) is an acquired autoimmune disorder that results from accelerating platelet clearance, destruction, and production. Front-line therapy for newly diagnosed ITP includes corticosteroids, intravenous immune globulin, or anti-D immunoglobulin. However, after these single-agent therapies, relapses will occur in half of patients. We previously reported the safety, feasibility, and efficacy of the combination of dexamethasone, low-dose rituximab, and the thrombopoietin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is the only TPO-RA, which is administered subcutaneously and its initial dose is 1 mg/kg per week, with dose adjustments according to platelet response [42,43]. [46]. Furthermore, Kikuchi et al [47] concluded in their study that addition of rituximab to standard therapy (romiplostim and splenectomy) decreases treatment costs and increases efficacy in ITP adults in Japan, compared with the ones in standard therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the only TPO-RA, which is administered subcutaneously and its initial dose is 1 mg/kg per week, with dose adjustments according to platelet response [42,43]. [46]. Furthermore, Kikuchi et al [47] concluded in their study that addition of rituximab to standard therapy (romiplostim and splenectomy) decreases treatment costs and increases efficacy in ITP adults in Japan, compared with the ones in standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Colunga-Pedraza et al in their pilot study showed that all but one patient who received rituximab (100 mg weekly, four doses) and romiplostim (2 μg/kg weekly, four times a week) and dexamethasone (40 mg p.o. days 1–4) achieved response (CR or PR) at a median of 7 days [46]. Furthermore, Kikuchi et al [47] concluded in their study that addition of rituximab to standard therapy (romiplostim and splenectomy) decreases treatment costs and increases efficacy in ITP adults in Japan, compared with the ones in standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several single-arm studies reported that HD-DXM in combination with eltrombopag had favorable SRR at 6 months (56.5–75%) and good tolerability in newly diagnosed treatment-naïve ITP patients [ 111 , 112 ]. In addition, more intensified strategies using the combination of eltrombopag or romiplostim, low-dose rituximab, and HD-DXM have been proposed and tested in small pilot studies [ 113 , 114 ]; however, the improvement in relapse-free survival yielded by the three-drug combination still needs validation. In a large prospective RCT, we recently showed that HD-DXM plus a limited course of recombinant human thrombopoietin (rhTPO) elicited a higher response rate at day 14 and month 6, and a slightly higher treatment-free remission rate thereafter than HD-DXM monotherapy [ 115 ].…”
Section: Initial Treatmentmentioning
confidence: 99%